Perfil alimentar e avaliação do conhecimento nutricional de jogadoras de esportes coletivos - Araújo, Márcia Matsumura de (2012)
This study aimed to evaluate the food consumed by female players of team sports in high school, to assess the diet quality index and the nutrition knowledge of these players. The dietary intake was assessed through food records from 4 days, the Diet Quality Index and nutrition knowledge through a validated questionnaire. The group had a mean age of 16.8 years (± 1.5). The inadequacies of the diet found were: Low average energy consumption (1621,9Kcal); Inadequacie of carbohydrate (90.9%), proteins (81.8%) and lipids (50%). There were also found inadequacies for vitamins A (63.6%) and C (59.1%). The inadequacie minerals were: calcium (59.1%), phosphate (95.5%), zinc (77.3%) and electrolytes as sodium (100%) and potassium (100%). In addition, inadequate intake of fiber was found in 100% of the sample. As for the Diet Quality Index, 72.7% require modification of their diets and nutrition knowledge was moderate (72.5%). The analysis of food intake showed that players consume an inadequate diet for their health and physical performance and the Diet Quality Index, together with the assessment of nutrition knowledge show that athletes have moderate knowledge about nutrition but need changes in their diets, suggesting the need for nutritional intervention in this group.